Ten years of negotiating rights around maternal health in Uttar Pradesh, India - Dasgupta Jashodhara (BMC, 2011)
Abstract Background Preventable maternal mortality and morbidity have been globally recognized as human rights issues. Maternal mortality in India is among the highest in the world, and reflects inequity in access to healthcare: women from certain states as well as poorer women and less literate women appear to be significantly disadvantaged. The government of India has been attempting to improve maternal outcomes through a cash transfer within the National Rural Health Mission to encourage women to come to hospitals for childbirth. Methods This paper reviews documents of the last ten years describing the experiences of a Non-Governmental Organisation, SAHAYOG, in working with a civil society platform, the Healthwatch Forum, to develop 'rights based' strategies around maternal health. The paper builds an analysis using recent frameworks on accountability and gendered rights claiming to examine these experiences and draw out lessons regarding rights claiming strategies for poor women. Results The examination of documents over the last ten years indicates defined phases of development in the evolution of SAHAYOG's understanding and of the shifts in strategy among SAHAYOG and its close allies, and responses by the state. The first three stages depict the deepening of SAHAYOG's understanding of the manner in which poor and marginalized women negotiate their access to health care; the fourth stage explores a health system intervention and the challenges of working from within civil society in alliance with poor and marginalized women. Conclusion The findings from SAHAYOG's experiences with poor Dalit women in Uttar Pradesh reveal the elements of social exclusion within the health system that prevent poor and marginalized women from accessing effective lifesaving care. Creating a voice for the most marginalised and carving space for its articulation impacts upon the institutions and actors that have a duty to meet the claims being made. However, given the accountability deficit, the analysis indicates the importance of going beyond the normative to developing actor-oriented perspectives within rights based approaches, to take into account the complexity of the negotiating process that goes into claiming any kind of entitlements.